2 Age-Related Disparities in Clinical Characteristics and Survival Outcomes of High-Grade Spinal Cord Gliomas: A Retrospective Analysis of 219 Patients - Khalid Sarhan; Mohammed A Azab (Neuro-Oncology, 2026)
Abstract Introduction High-grade spinal cord gliomas exhibit significant age-dependent disparities in survival and clinical management. This study evaluates how age influences prognosis and the utilization of treatment modalities like radiation and chemotherapy. Methods A retrospective analysis was conducted on 219 patient records, categorized into four age groups: Children (N = 41), AYA (N = 71), Older adults (N = 76), and Elderly (N = 31). Statistical measures included median survival, 1, 3, and 5-year survival rates, and Cox proportional hazards regression to determine mortality risk. Treatment modalities, specifically the administration of radiation therapy, were compared across age categories using chi-square testing. Results Significant age-related disparities were found in tumor types (P = 0.032), radiation treatment (P = 0.012), and overall survival (P < 0.013). Notably, the elderly cohort was significantly less likely to receive radiation, with 50% of these patients not receiving the treatment, compared to only 20% of children and 10% of AYA patients. Median survival was highest in children (59.5 months) and lowest in the elderly (10 months). Cox regression identified the elderly group as having the highest mortality risk (HR 3.01, p < 0.001) relative to children. In a sub-analysis of 90 glioblastoma cases, the risk of death was significantly increased for older adults (HR 1.92) and elderly (HR 2.41) patients compared to the AYA group. Conclusion Age is a critical determinant of survival in high-grade spinal cord gliomas. Elderly patients experience significantly poorer outcomes, which may be driven by more aggressive tumor biology and the observed decrease in the administration of radiation therapy within this population. These findings underscore the need for age-specific therapeutic strategies to address the high mortality risk in older patients.